Tax reform and labour-market performance in the euro area: a simulation-based analysis using the New Area-Wide Model - Günter Coenen; Peter McAdam; Roland Straub (European Central Bank (ECB), 2007)
In this paper, we employ a calibrated two-country version of the New Area-Wide Model (NAWM) currently under development at the European Central Bank to examine the potential benefits and spillovers of reducing labour-market distortions caused by euro area tax structures. Our analysis shows that lowering tax distortions to levels prevailing in the United States would result in an increase in hours worked and output by more than 10 percent. At the same time, tax reductions would have positive spillovers to the euro area's trade partners, bolstering the case for tax reforms from a global perspective. Finally, we illustrate that, in the presence of heterogeneous households, distributional effects may be of importance when gauging the impact of tax reforms.
Keywords: E32; E62; 330; DSGE modelling; euro area; Fiscal Policy; limited asset-market participation; tax reform; Arbeitsmarkt; Steuerreform; Eurozone; EU-Staaten